A Study of Subtitle Translation of English Taboo Words into Thai in Adult Animated Series entitled Big Mouth: การศึกษาการแปลถ้อยคำต้องห้ามในบทบรรยายใต้ภาพชุดการ์ตูนแอนิเมชันสำหรับผู้ใหญ่ เรื่อง Big Mouth จากภาษาอังกฤษเป็นภาษาไทย - เถาวัลย์, ชนัญชิดา (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2021)
The objectives of this paper are to study translation strategies of taboo words by using translation strategies proposed by Baker (2018) as a framework and to study the frequency of each strategy. Taboo word translations are collected from Thai subtitles of adult animated series entitled Big Mouth including season 1, 2, and 3 since it represents taboos such as sex, diseases, and addressing, leading to frequent occurrences of taboo words in the characters’ conversations. The results reveal that there are eight translation strategies: using cultural substitution (26.88%), using a more neutral/less expressive word (26.07%), literal translation (16.35%), using a more general word (12.41%), omitting words (8.65%), paraphrasing with unrelated words (5.83%), paraphrasing with related words (3.51%), and using a loan word or loan word plus explanation (0.31%). Using cultural substitution is the most common translation strategy, followed by using a more neutral/less expressive word. Using a loan word or loan word plus explanation is the least frequent method.